The diagnostic accuracy of magnetic resonance venography in the detection of deep venous thrombosis: a systematic review and meta-analysis. Issue 8 (August 2015) - Abdalla, G.; Fawzi Matuk, R.; Venugopal, V.; Verde, F.; Magnuson, T.H.; Schweitzer, M.A.; Steele, K.E.
<x xml:space="preserve">Abstract</x> Aim To search the literature for further evidence for the use of magnetic resonance venography (MRV) in the detection of suspected DVT and to re-evaluate the accuracy of MRV in the detection of suspected deep vein thrombosis (DVT). Materials and methods PubMed, EMBASE, Scopus, Cochrane, and Web of Science were searched. Study quality and the risk of bias were evaluated using the QUADAS 2. A random effects meta-analysis including subgroup and sensitivity analyses were performed. Results The search resulted in 23 observational studies all from academic centres. Sixteen articles were included in the meta-analysis. The summary estimates for MRV as a diagnostic non-invasive tool revealed a sensitivity of 93% (95% confidence interval [CI]: 89% to 95%) and specificity of 96% (95% CI: 94% to 97%). The heterogeneity of the studies was high. Inconsistency (I2) for sensitivity and specificity was 80.7% and 77.9%, respectively. Conclusion Further studies investigating the use of MRV in the detection of suspected DVT did not offer further evidence to support the replacement of ultrasound with MRV as the first-line investigation. However, MRV may offer an alternative tool in the detection/diagnosis of DVT for whom ultrasound is inadequate or not feasible (such as in the obese patient).